If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 17 = -4x + -27 Reorder the terms: 17 + 2x = -4x + -27 Reorder the terms: 17 + 2x = -27 + -4x Solving 17 + 2x = -27 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 17 + 2x + 4x = -27 + -4x + 4x Combine like terms: 2x + 4x = 6x 17 + 6x = -27 + -4x + 4x Combine like terms: -4x + 4x = 0 17 + 6x = -27 + 0 17 + 6x = -27 Add '-17' to each side of the equation. 17 + -17 + 6x = -27 + -17 Combine like terms: 17 + -17 = 0 0 + 6x = -27 + -17 6x = -27 + -17 Combine like terms: -27 + -17 = -44 6x = -44 Divide each side by '6'. x = -7.333333333 Simplifying x = -7.333333333
| 3(8+g)+5g=0 | | 4t-1(2t+3u)= | | x^2y^2-81z^2=0 | | x^2=1.8225 | | 2m+3n+1for-1=m | | 95=5x-45 | | 8w+5-2w=101 | | 4n+7n-3=96 | | -10.6=w/8+22 | | 3x(23+5x)=14 | | 3x^2+3y^2-36=0 | | 3x=5x-24 | | 16=-12-7x | | 3(4x-2)=2+12x-3 | | 4(y+3)=34 | | 8x+6=-106 | | 120-5(u-5)=9(7u-5) | | 3y-7y-9+5=-2y-18+3y+13 | | 12-0.5(u-5)=0.9(7u-5) | | -2+4b=8+2b | | 13.95a+1.95=99.60 | | 2x+1-3x=3(x+10) | | 5x+15=9x-13 | | 7(x+5)=-7(x+-35) | | (X+1)(2x^2-9x+9)= | | 0.6y-1.5=0.3y | | 180-7(m-120)=4(40m-12) | | f-7.625=1.833333+d | | 6p+-48=-6p+12 | | 13x-7=9x+1 | | 6p+-48=6p+12 | | x-16=6(x-2) |